Freedom's sword : the NAACP and the struggle against racism in America, 1909-1969 - Jonas, Gilbert (New York : Routledge, 2005)
Freedom's Sword is the first history to detail the remarkable, lasting achievements of the NAACP's first sixty years. From its pivotal role in overturning the Jim Crow laws in the South to its twenty-year court campaign that culminated with Brown v. the Board of Education, the NAACP has been at the forefront of the struggle against American racism. Gilbert Jonas, a fifty-year veteran of the organization, tracks America's political and social landscape period by period, as the NAACP grows to 400,000 members and is recognized by both blacks and whites as the leading force for social jus.
Creating a change agent : the NAACP's early years -- The law as a weapon against unjust laws -- Southern retaliation against Negro determination -- Leading the African-American quest for political power -- Comes the revolution : the struggle between the NAACP and the Communist Party USA -- World War II and its consequences for race -- The politics of political advancement -- Revolution at the ballot box -- Black workers, white unions, and the struggle for job equality -- Head to head with the Garment Workers Union -- The end of pretense : organized labor refuses to desegregate -- Roy Wilkins : the gentle giant -- The NAACP develops financial muscle.
Includes bibliographical references (pages 471-480) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: National Association for the Advancement of Colored People -- History; National Association for the Advancement of Colored People; African Americans -- Civil rights -- History -- 20th century; Civil rights movements -- United States -- History -- 20th century; African Americans -- Politics and government -- 20th century; Racism -- United States -- History -- 20th century; United States -- Race relations; Noirs américains -- Droits -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Politique et gouvernement -- 20e siècle.; Racisme -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations raciales; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; African Americans -- Civil rights; African Americans -- Politics and government; Civil rights movements; Race relations; Racism; United States; 1900-1999; Electronic books; History